Information for contributors and readers for issue 4-2020 (Vojnotehnički glasnik / Military Technical Courier, 2020)
2020 Award and acknowledgments for the best reviewersThe Serbian citation index has completed the evaluation of reviewers for 2020. The award ceremony for the best reviewers was held at the CEON office in Belgrade, on Friday, September 25.